Mechanisms underlying response and resistance to immune checkpoint blockade in cancer immunotherapy - Lee, Junghwa; Kim, Eui Ho (Frontiers in Oncology, 2023)
Cancer immunotherapies targeting immune checkpoint pathways, such as programmed cell death-1 (PD-1)/programmed cell death 1 ligand-1 (PD-L1) and cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4), have achieved unprecedented therapeutic success in treating various types of cancer. The prominent and persistent clinical responses to immune checkpoint blockade (ICB) therapy are currently constrained to a subset of patients. Owing to discrete individual tumor and immune heterogeneity, most patients fail to benefit from ICB treatment, demonstrating either primary or acquired resistance. A thorough comprehension of the mechanisms restricting the efficacy of immune checkpoint inhibitors (ICIs) is required to extend their clinical applicability to a broader spectrum of patients and cancer types. Numerous studies are presently investigating potential prognostic markers of responsiveness, the complex dynamics underlying the therapeutic and adverse effects of ICB, and tumor immune evasion throughout the course of immunotherapy. In this article, we have reviewed the extant literature elucidating the mechanisms underlying the response and resistance to ICB, with a particular emphasis on PD-1 and CTLA-4 pathway blockade in the context of anti-tumor immunity. Furthermore, we aimed to explore potential approaches to overcome cancer therapeutic resistance and develop a rational design for more personalized ICB-based combinational regimens.